Battery sampling branch structure
By bonding reinforcement patches to the back of the copper foil substrate of the battery sampling branch structure and forming conductive connections, combined with laser welding technology, the problems of structural deformation, insufficient connection strength and complex welding process are solved, and an efficient and reliable manufacturing process is achieved.
Patent Information
- Application Number
- CN202510059107.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-15
AI Technical Summary
The battery sampling branch structure is prone to deform during welding, the connection strength is insufficient, and additional reinforcement is required. The welding process is complex and the production efficiency is low.
A copper foil substrate is used and reinforcement patches are bonded to the back of it, and conductive connections are formed through conductive glue, and fixed connections are made with the insulating layer windows through laser welding to enhance the rigidity and connection strength of the structure.
It effectively avoids structural deformation, improves welding strength and working hours efficiency, reduces production costs, and does not require additional dispensing and reinforcement.
Smart Images

Figure CN119833905A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery sampling branch structures, and in particular to a battery sampling branch structure. Background Art
[0002] In the field of design and manufacturing of battery sampling branch structures, although there are many technical solutions, each solution faces some common challenges and problems. These problems not only affect the production efficiency and quality stability of the product, but also may increase production costs and complexity.
[0003] First, the welding area and connection parts of the sampling branch are prone to deformation. This may be caused by thermal stress or mechanical stress generated during the welding process. The deformation not only affects the appearance quality of the product, but may also have an adverse effect on the subsequent manufacturing process, such as assembly difficulties and poor contact.
[0004] Secondly, low connection strength with aluminum bars or other metal parts is a common problem. This may be caused by improper selection of welding materials, welding processes or welding parameters. Low connection strength may cause product failures such as loosening, falling off or breaking during long-term use, thus affecting the performance and safety of the battery.
[0005] In addition, in order to improve the connection strength or prevent defects during welding, additional reinforcement measures are often required, such as dispensing, laminating, or increasing the welding area, etc. These measures not only increase production costs and complexity, but may also have a negative impact on product reliability and stability.
[0006] In addition, the low efficiency of welding time is also a problem that cannot be ignored. In the large-scale production process, the efficiency of welding time directly affects the production cycle and cost of the product. If the welding process is too complicated or time-consuming, it will be difficult to meet market demand and cost control requirements.
[0007] In summary, there are many challenges and problems in the design and manufacturing process of battery sampling branch structures, including deformation, low connection strength, additional reinforcement measures, and low welding time efficiency. In order to overcome these challenges, continuous exploration and innovation are needed to develop more efficient, reliable, and economical manufacturing solutions. This may involve research and practice in improving welding processes, optimizing material selection, and improving automation levels. Summary of the invention
[0008] In order to overcome the shortcomings of the existing technical solutions, the present invention provides a battery sampling branch structure, which can effectively solve the problems proposed in the background technology that the battery sampling branch structure is easy to deform during welding, the strength of the connecting aluminum bar is insufficient and additional reinforcement is required, and the overall welding process is complicated and the production efficiency is low.
[0009] The technical solution adopted by the present invention to solve the technical problem is: a battery sampling branch structure, comprising: a copper foil substrate, the copper foil substrate is hollowed out in the middle and an insulating layer window is arranged on the back; A reinforcing patch, wherein the reinforcing patch is attached to the back of the copper foil substrate, and a conductive adhesive is applied to the attachment surface of the reinforcing patch or the back of the copper foil substrate to form a conductive connection between the reinforcing patch and the copper foil substrate; Wherein, the reinforcing patch is fixedly connected to the opening of the insulating layer by laser welding.
[0010] Furthermore, it also includes a routing area, which is arranged around the copper foil hollow area and exceeds the window area of the insulation layer.
[0011] Furthermore, it also includes a hot pressing area, which is arranged on the back side of the copper foil substrate and surrounds the copper foil hollow area.
[0012] Furthermore, the shape of the hot pressing area is a rounded rectangle.
[0013] Furthermore, the reinforcing patch includes at least one of a stainless steel sheet, a copper metal sheet, a nickel metal sheet, an aluminum metal sheet and a titanium metal sheet.
[0014] Furthermore, the bonding surface of the reinforcing patch completely covers or exceeds the window area of the insulating layer.
[0015] Furthermore, the conductive adhesive is in a hollow rectangular shape when laid flat, and completely covers or exceeds the window area of the insulating layer.
[0016] Furthermore, the width of the conductive adhesive after being laid flat is greater than 1 mm.
[0017] Furthermore, the thickness of the conductive adhesive after being laid flat is less than 2 mm.
[0018] An integrated busbar comprises the battery sampling branch structure as described in any one of claims 1 to 9.
[0019] Compared with the prior art, the beneficial effects of the present invention are: the sampling branch structure with the added reinforcement patch has a certain rigidity, which effectively avoids deformation; the welding method is laser welding, the welding strength is high, and the welding time efficiency is high; and there is no need for glue reinforcement, which reduces costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a structural schematic diagram of the present invention; Figure 2 The structure of the present invention is Figure 1 ; Figure 3 The structure of the present invention is Figure 2 ; Figure 4It is a structural cross-sectional view of the present invention; Figure 5 It is a stereoscopic diagram of the integrated busbar of the present invention.
[0021] Numbers in the figure: 1-Copper foil substrate, 2-Reinforcement patch, 3-Tracking area, 4-Insulation layer window, 5-Conductive adhesive, 6-Hollowout, 7-Hot pressing area. DETAILED DESCRIPTION
[0022] The embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.
[0023] The following describes the embodiments of the present disclosure through specific examples, and those skilled in the art can easily understand other advantages and effects of the present disclosure from the contents disclosed in this specification. Obviously, the described embodiments are only a part of the embodiments of the present disclosure, rather than all of the embodiments. The present disclosure can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present disclosure. It should be noted that the following embodiments and features in the embodiments can be combined with each other without conflict. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present disclosure.
[0024] like Figure 1-5 As shown, the present invention provides a battery sampling branch structure, comprising: a copper foil substrate 1, the copper foil substrate 1 is hollowed out in the middle and an insulating layer window 4 is provided on the back, and the insulating layer window 4 is used to expose a part of the copper foil; The reinforcing patch 2 is attached to the back of the copper foil substrate 1. The conductive adhesive 5 is applied to the attachment surface of the reinforcing patch 2 or the back of the copper foil substrate 1 to form a conductive connection between the reinforcing patch 2 and the copper foil substrate 1, so that the product body has a certain rigidity and meets the conditions for laser welding. The reinforcing patch 2 is fixedly connected to the insulating layer window 4 by laser welding.
[0025] The reinforcing patch 2 forms a conductive connection with the copper foil substrate 1 through the conductive adhesive 5, which enhances the connection strength between the copper foil substrate 1 and the subsequent electronic components or circuit boards, and reduces the risk of the copper foil falling off or being damaged during welding. The reinforcing patch 2 provides additional support for the copper foil substrate 1, increases the support strength of the board on the copper foil substrate 1, and improves the impact resistance of the entire structure. The use of the reinforcing patch 2 helps to improve the overall reliability and stability of the battery sampling branch structure, ensuring that the battery can maintain stable performance during long-term use.
[0026] Laser welding can achieve a high-precision fixed connection between the reinforcing patch 2 and the insulating layer window 4, ensuring that the position between the two is accurate and the connection is firm.
[0027] Laser welding has the characteristics of high speed and high heat, but the welding process is very short, and the laser soldering machine is equipped with a temperature control function, so the thermal impact on the copper foil substrate 1 and the insulation layer is small, reducing the thermal damage and deformation that may occur during the welding process.
[0028] Through laser welding, a tight connection is formed between the reinforcing patch 2 and the insulating layer window 4, thereby improving the sealing of the entire structure and preventing interference and erosion from the external environment.
[0029] Laser welding not only realizes the mechanical connection between the reinforcing patch 2 and the insulating layer window 4, but also ensures the conductive connection between the reinforcing patch 2 and the copper foil substrate 1 through the conductive adhesive 5, thereby ensuring the electrical performance of the battery sampling branch structure.
[0030] Furthermore, it also includes a routing area 3, which is arranged around the copper foil hollow area and exceeds the insulating layer window 4 area.
[0031] The routing area 3 allows enough space for the battery sampling lines to be arranged, avoiding crossing and interference between lines, thereby ensuring stable signal transmission and helping to reduce faults and performance degradation caused by improper line layout.
[0032] The copper foil hollow area is used to realize the connection between the battery management controller and the battery information collector. The routing area 3 is set around the hollow area to provide additional protection for it.
[0033] Furthermore, it also includes a hot pressing area 7, which is arranged on the back of the copper foil substrate 1 and surrounds the copper foil hollow area. It is used to ensure the accurate position of the reinforcement patch through hot pressing when the reinforcement patch is attached, prevent displacement, and enhance the bonding strength.
[0034] In the process of attaching the reinforcement patch, the hot pressing area 7 ensures that the reinforcement patch can be accurately attached to the predetermined position of the copper foil substrate 1 through the high temperature and high pressure environment. During the hot pressing process, the high temperature and high pressure work together to form a strong bond between the reinforcement patch and the copper foil substrate 1. Not only does it enhance the bonding strength, it also effectively prevents the reinforcement patch from being offset during use, which helps to maintain the stability and reliability of the battery sampling branch structure.
[0035] Furthermore, the shape of the hot pressing area 7 is a rounded rectangle.
[0036] The rounded rectangular design can disperse stress more effectively and reduce structural damage caused by stress concentration.
[0037] The rounded rectangular shape is easier to process and position during production. This shape design can simplify the production process, improve production efficiency, and reduce production errors and cost increases caused by complex shapes.
[0038] The rounded rectangular heat pressing area 7 design can ensure the accuracy of the enhanced patch during the bonding process. Since the rounded rectangular shape is more regular, it is easier to achieve precise alignment and positioning during the bonding process, thereby improving the accuracy and reliability of the bonding.
[0039] Furthermore, the reinforcing patch 2 includes at least one of a stainless steel sheet, a copper metal sheet, a nickel metal sheet, an aluminum metal sheet and a titanium metal sheet.
[0040] Stainless steel sheet: Stainless steel has excellent corrosion resistance and is highly versatile; when laser welding stainless steel sheets, the weld is smooth and beautiful, and the welding strength is high.
[0041] Aluminum sheet: Aluminum is highly versatile due to its lightness and corrosion resistance. Although aluminum has a high reflectivity, laser welding technology can still effectively weld aluminum sheets.
[0042] Copper sheet: Copper has good electrical and thermal conductivity and is highly versatile. When laser welding copper sheets, it is necessary to select appropriate welding parameters and processes to ensure the quality of the weld.
[0043] Nickel sheet: Nickel has high corrosion resistance and is suitable for some special fields. When laser welding nickel sheets, it is also necessary to pay attention to problems such as thermal cracks and pores during the welding process.
[0044] Titanium sheet: Titanium sheet is light in weight and high in strength, and is suitable for aviation, medical and other fields. When laser welding titanium sheets, appropriate welding methods and protective measures need to be adopted to ensure the quality and strength of the weld.
[0045] Furthermore, the bonding surface of the reinforcing patch 2 completely covers or exceeds the area of the opening 4 of the insulating layer to ensure the conductive connection effect after bonding.
[0046] The bonding surface of the reinforcing patch 2 completely covers the insulating layer window 4 area, which can ensure that the conductive connection part forms good electrical contact with other parts of the battery sampling branch structure, which helps to reduce contact resistance and improve current transmission efficiency, thereby ensuring the normal operation of the battery system.
[0047] Through the design of fitting beyond the insulating layer window 4 area, the reinforcing patch 2 is not only connected to the conductive part in the insulating layer window 4 area, but also forms an additional connection with the part around the window area. This design increases the redundancy of the connection and improves the fault tolerance rate.
[0048] The bonding surface of the reinforcing patch 2 completely covers or exceeds the area of the insulating layer window 4, which also helps to enhance the durability of the battery sampling branch structure. The reinforcing patch 2 can provide better mechanical support and reduce the risk of loose connection or breakage caused by external stress or vibration.
[0049] Furthermore, the conductive adhesive 5 is in a hollow rectangular shape when laid flat, and completely covers or exceeds the area of the opening 4 of the insulating layer, so as to ensure the conductive connection effect after bonding.
[0050] The conductive glue 5 is laid flat in a hollow rectangular shape and completely covers the insulating layer window 4 area, which can ensure that the conductive connection part forms good electrical contact with other parts of the battery sampling branch structure. This design reduces the problem of increased contact resistance caused by incomplete conductive connection, thereby improving current transmission efficiency.
[0051] The conductive adhesive 5 not only covers the area of the insulating layer window 4, but also extends beyond the area to form an additional connection area. This design increases the redundancy of the connection. Even if some connection points become loose or fail due to external factors (such as vibration, temperature change, etc.), the stability of the conductive connection can be maintained through other connection points.
[0052] The flattened state of the conductive glue 5 and its design beyond the area of the insulating layer window 4 provide additional mechanical support for the battery sampling branch structure. This helps reduce the risk of loose connection or breakage due to external stress or vibration, thereby improving the durability of the structure.
[0053] Furthermore, the width of the conductive adhesive 5 after being laid flat is greater than 1 mm.
[0054] The conductive performance of the conductive adhesive 5 is related to its spreading area. When the width of the conductive adhesive 5 after spreading is greater than 1 mm, a larger conductive contact area can be formed, thereby effectively reducing the contact resistance and improving the conductive performance.
[0055] Furthermore, the thickness of the conductive adhesive 5 after being laid flat is less than 2 mm.
[0056] The main function of the conductive adhesive 5 is to conduct electricity, and its conductive performance is related to the thickness of the adhesive layer. Although the thickness affects the resistivity (usually the thinner the thickness, the lower the resistivity), in practical applications, a thickness of less than 2 mm is usually sufficient to ensure a good conductive connection. Conductive adhesive 5 of this thickness can effectively fill the tiny gaps between electronic components, forming a continuous conductive path and ensuring stable transmission of current.
[0057] In precision electronic assembly, there are strict requirements for the thickness of the conductive adhesive 5. A thickness of less than 2 mm allows the conductive adhesive 5 to more flexibly adapt to various complex structures and tiny spaces, ensuring precise connections between electronic components. This thickness of conductive adhesive 5 not only helps reduce errors during assembly, but also improves the overall performance and reliability of electronic products.
[0058] An integrated busbar comprises a battery sampling branch structure as claimed in any one of claims 1 to 9.
[0059] The sampling branch structure of the integrated busbar with the additional reinforcement patch 2 has a certain rigidity, which effectively avoids deformation; the welding method is laser welding, which has high welding strength and high welding time efficiency; and there is no need for glue reinforcement, which reduces costs. Embodiment 1
[0060] The battery sampling branch structure of this embodiment includes a copper foil substrate 1, a hollow area is provided in the middle of the copper foil substrate 1, and an insulating layer window 4 is provided on the back thereof to expose part of the copper foil. The reinforcing patch 2 is made of a stainless steel sheet, which is bonded to the back of the copper foil substrate 1, and is electrically connected to the copper foil substrate 1 through a conductive adhesive 5 (a hollow rectangular shape in a flat state, with a width of 1.5 mm and a thickness of 1 mm). The bonding surface of the reinforcing patch 2 completely covers the insulating layer window 4 area. In addition, the structure also includes a routing area 3, which is arranged around the copper foil hollow area and exceeds the insulating layer window 4 area. The reinforcing patch 2 is fixedly connected to the insulating layer window 4 by laser welding to ensure the stability and sealing of the structure.
[0061] Differences: The reinforcing patch 2 is made of a stainless steel sheet.
[0062] The conductive adhesive 5 is in a hollow rectangular shape when laid flat, with a width of 1.5 mm and a thickness of 1 mm.
[0063] Advantages: Stainless steel sheets have good corrosion resistance and high strength and are suitable for a variety of environments.
[0064] The size of the conductive adhesive 5 is moderate, which can ensure the conductive performance and control the cost.
[0065] The structure is relatively simple and easy to manufacture and assemble. Embodiment 2
[0066] The battery sampling branch structure of this embodiment is similar to that of embodiment 1, but the reinforcing patch 2 uses a copper metal sheet. The hot pressing area 7 is set on the back of the copper foil substrate 1, surrounding the hollow area of the copper foil, and has a rounded rectangular shape. When the reinforcing patch is attached, hot pressing is used to ensure the accurate position of the reinforcing patch, prevent displacement, and enhance the bonding strength. The conductive glue 5 is also laid flat in a hollow rectangular shape, completely covering the insulating layer window 4 area, with a width of 2 mm and a thickness of 1.5 mm to ensure a good conductive connection effect.
[0067] Differences: The reinforcing patch 2 is made of a copper metal sheet.
[0068] A heat pressing area 7 is provided, which is in the shape of a rounded rectangle.
[0069] The conductive adhesive 5 is in a hollow rectangular shape when laid flat, with a width of 2 mm and a thickness of 1.5 mm.
[0070] Advantages: The copper metal sheet has good electrical and thermal conductivity, which helps to improve the overall performance of the battery sampling branch structure.
[0071] The hot pressing area 7 improves the bonding accuracy and strength between the reinforcing patch 2 and the copper foil substrate 1 .
[0072] The conductive adhesive 5 is larger in size, providing a more reliable conductive connection. Embodiment 3
[0073] The battery sampling branch structure of this embodiment uses a nickel metal sheet as a reinforcing patch 2. The arrangement of the copper foil substrate 1, the insulating layer window 4 and the reinforcing patch 2 is similar to that of Example 1. The difference is that the bonding surface of the reinforcing patch 2 exceeds the insulating layer window 4 area, and the width of the conductive adhesive 5 after flattening is 1 mm, but the thickness is 0.8 mm, so as to improve the flexibility of the structure while ensuring the conductive performance.
[0074] Differences: The reinforcing patch 2 is made of a nickel metal sheet.
[0075] The bonding surface of the reinforcing patch 2 exceeds the area of the opening 4 of the insulating layer.
[0076] The conductive adhesive 5 has a width of 1 mm after being laid flat, but a thickness of 0.8 mm.
[0077] Advantages: Nickel sheet metal has high corrosion resistance and strength.
[0078] The bonding surface of the reinforcing patch 2 exceeds the area of the opening 4 of the insulating layer, thereby increasing the bonding surface and improving the overall strength of the copper foil substrate 1.
[0079] The thickness of the conductive adhesive 5 is relatively thin, which improves the flexibility of the structure. Embodiment 4
[0080] The battery sampling branch structure of this embodiment uses an aluminum metal sheet as a reinforcing patch 2. The copper foil substrate 1 is hollowed out in the middle, and an insulating layer window 4 is provided on the back. The reinforcing patch 2 is conductively connected to the copper foil substrate 1 through a conductive adhesive 5 (1.2 mm wide and 1 mm thick). In order to improve the fitting accuracy and strength, a hot pressing area 7 is provided in the shape of a rounded rectangle. The reinforcing patch 2 is fixedly connected to the insulating layer window 4 by laser welding to ensure the stability and sealing of the structure. In addition, the design of the routing area 3 focuses on avoiding line crossing and interference.
[0081] Differences: The reinforcing patch 2 is made of an aluminum metal sheet.
[0082] A heat pressing area 7 is provided, which is in the shape of a rounded rectangle.
[0083] The conductive adhesive 5 is in a hollow rectangular shape when laid flat, with a width of 1.2 mm and a thickness of 1 mm.
[0084] Advantages: Aluminum sheet metal is lightweight and corrosion-resistant, helping to reduce the weight of the battery sampling branch structure.
[0085] The heat pressing area 7 improves the bonding accuracy and strength.
[0086] The size of the conductive adhesive 5 is moderate, which can ensure the conductive performance and control the cost. Embodiment 5
[0087] The battery sampling branch structure of this embodiment uses a titanium metal sheet as the reinforcing patch 2. The arrangement of the copper foil substrate 1, the insulating layer window 4 and the reinforcing patch 2 is similar to that of other embodiments. The conductive adhesive 5 is laid in a hollow rectangular shape with a width of 1.8 mm and a thickness of 1.2 mm to ensure a good conductive connection effect and the durability of the structure. The hot pressing area 7 is also set as a rounded rectangle to improve the fitting accuracy and strength. The reinforcing patch 2 is fixedly connected to the insulating layer window 4 by laser welding to ensure the stability and sealing of the entire structure. In addition, this embodiment also pays attention to the covering relationship between the conductive adhesive 5 and the reinforcing patch 2 and the insulating layer window 4 area to ensure the conductive connection effect after bonding.
[0088] Differences: The reinforcing patch 2 is made of a titanium metal sheet.
[0089] The conductive adhesive 5 is in a hollow rectangular shape when laid flat, with a width of 1.8 mm and a thickness of 1.2 mm.
[0090] The hot pressing area 7 is configured as a rounded rectangle.
[0091] Pay attention to the covering relationship between the conductive adhesive 5 and the reinforcing patch 2 and the opening 4 area of the insulating layer.
[0092] Advantages: Titanium sheet metal is lightweight and high in strength, making it suitable for applications where weight and strength are critical.
[0093] The conductive adhesive 5 is larger in size, providing a more reliable conductive connection and structural durability.
[0094] The covering relationship between the hot pressing area 7 and the conductive adhesive 5 ensures the conductive connection effect after bonding, and improves the stability and sealing of the battery sampling branch structure.
[0095] In the description of the present invention, it is necessary to understand that the terms "middle", "length", "up", "down", "front", "back", "vertical", "horizontal", "inside", "outside", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.
[0096] In the present invention, unless otherwise clearly specified and limited, the first feature "on" the second feature may be that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. "Multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically limited.
[0097] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral one; it can be a mechanical connection, an electrical connection, or communication with each other; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements, unless otherwise clearly defined. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0098] The above is only for explaining the implementation mode of the present invention and is not intended to limit the present invention. For those skilled in the art, any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention without creative work should be included in the protection scope of the present invention.
Claims
1. A battery sampling branch structure, characterized in that: include: A copper foil substrate, wherein the copper foil substrate is hollowed out in the middle and an insulating layer window is provided on the back; A reinforcing patch, wherein the reinforcing patch is attached to the back of the copper foil substrate, and a conductive adhesive is applied to the attachment surface of the reinforcing patch or the back of the copper foil substrate to form a conductive connection between the reinforcing patch and the copper foil substrate; Wherein, the reinforcing patch is fixedly connected to the opening of the insulating layer by laser welding.
2. A battery sampling branch structure according to claim 1, characterized in that: It also includes a routing area, which is arranged around the copper foil hollow area and exceeds the window area of the insulation layer.
3. A battery sampling branch structure according to claim 1 or 2, characterized in that: It also includes a hot pressing area, which is arranged on the back side of the copper foil substrate, and the hot pressing area overlaps with the conductive adhesive covering area.
4. A battery sampling branch structure according to claim 3, characterized in that: The shape of the hot pressing area is a rounded rectangle.
5. A battery sampling branch structure according to claim 1, characterized in that: The reinforcing patch includes at least one of a stainless steel sheet, a copper metal sheet, a nickel metal sheet, an aluminum metal sheet and a titanium metal sheet.
6. A battery sampling branch structure according to claim 1, characterized in that: The bonding surface of the reinforcing patch completely covers or exceeds the window area of the insulating layer.
7. A battery sampling branch structure according to claim 1, characterized in that: The conductive adhesive is in a hollow rectangular shape when laid flat, and completely covers or exceeds the window area of the insulating layer.
8. A battery sampling branch structure according to claim 7, characterized in that: The width of the conductive adhesive after being laid flat is greater than 1 mm.
9. A battery sampling branch structure according to claim 7 or 8, characterized in that: The thickness of the conductive adhesive after being laid flat is less than 2 mm.
10. An integrated busbar, characterized in that: It comprises the battery sampling branch structure as described in any one of claims 1-9.